Assessment of the efficiency of prefabricated hybrid composite plates (HCPs) for retrofitting of damaged interior RC beam–column joints - Esmaeeli, Esmaeel (2015)
The effectiveness of prefabricated hybrid composite plates (HCPs) as a seismic retrofitting solution for damaged interior RC beam-column joints is experimentally studied. HCP is composed of a thin plate made of strain hardening cementitious composite (SHCC) reinforced with CFRP sheets/laminates. Two full-scale severely damaged interior beam-column joints are retrofitted using two different configurations of HCPs. The effectiveness of these retrofitting solutions mainly in terms of hysteretic response, dissipated energy, degradation of secant stiffness, displacement ductility and failure modes are compared to their virgin states. According to these criteria, both solutions resulted in superior responses regarding the ones registered in their virgin states.